Pengembangan Modul Digital Berbasis Google Sites pada Materi Sistem Pertahanan Tubuh Kelas XI: (Developing Digital Module Based Google Sites for Material Immune System for 11th Grade of Senior High School) - Camilla Masyita Yusha; Listika Yusi Risnani (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2023)
This research aims to produce a valid and practical web-based digital module (using Google Sites) for the topic of the immune system for the eleventh grade of senior high school. This study is a Development Research using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The instrument used was a questionnaire. The data collection technique for this research was in the form of a questionnaire. The data obtained were analyzed using the quantitative descriptive analysis technique. The research results show that the developed web-based digital module on Google Sites received a